Boundedness of Fractional Integrals with a Rough Kernel on the Product Triebel-Lizorkin Spaces (Communications in Mathematical Research, 2019)
By using the Littlewood-Paley decomposition and the interpolation theory, we prove the boundedness of fractional integral on the product Triebel-Lizorkinspaces with a rough kernel related to the product block spaces.